Study on Relationship between Material Vickers Hardness and Yield Stress of A508 Nuclear Material. Issue 1 (October 2020) - Zhuang, Zecheng; Lan, Minhua; Yao, Yinjing; Xu, Shichao; Xu, Jie
Abstract: It is difficult to directly obtain the mechanical properties of local materials of actual engineering structure (such as welded joints) by traditional mechanical test. Indentation test and ABAQUS finite element test were used in this paper, the relativity between Vickers hardness and yield stress of nuclear material A508 were studied, and a new method of using material surface Vickers hardness to acquire material properties was established. It can be used in the welded lines of nuclear dissimilar metal welded joints to obtain material parameters of mechanical property uneven zone of welded joints, and this new method was supported for complex engineering structure material mechanical parameters.